FORECAST OF TOURIST DEMAND IN UKRAINE ON A FAST-FUTURE PROSPECTS (World Science, 2018)
The process of formation of tourist demand was studied and autocorrelation and partial auto-correlation were calculated. Valued behavior of selective ACF and partial PACF, showing the hypothesis about the values of the parameters p and q. Due to the lack of data, several competing ARMA (1.1) and ARMA (2.0) models have been selected. Both models showed a good match with the data, the models are adequate and the errors are random, so the best model is chosen according to the AIC and BIC criterion. The remains of the selected model are checked for the absence of auto-correlation using the Lew Box test. For the selected best model, forecasts were projected for 5 periods ahead. From the forecast of the time series it is clear that the tourist demand in the next 5 years will decline.